Anti-corrosion composition, paint, coating and anode steel claw
By applying a coating of an anti-corrosion composition containing components such as hard clay, kaolin, etc. on the anode steel claw, the problem of corrosion and oxidation of anode steel claws in high temperature environments is solved, and a longer service life and more Low production costs.
Patent Information
- Application Number
- CN202411615662.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
Anode steel claws are susceptible to erosion by electrolytes, electrode feeding, air and electrolytic flue gas in high temperature environments, resulting in corrosion and oxidation, shortening service life and increasing production costs.
Using an anti-corrosion composition, including hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon powder and quartz sand, the plasticity of hard clay at high temperature is adjusted by reasonably designing the content of each raw material. , melting point and viscosity to form a coating with high temperature corrosion resistance.
It significantly improves the high-temperature gas corrosion performance of the anode steel claws, extends the service life, reduces production costs, and improves the quality of primary aluminum.
Smart Images

Figure CN119463554A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of coatings, and in particular to an anti-corrosion composition, a coating, a coating and an anode steel claw. Background Art
[0002] The electrolytic aluminum anode consists of three parts: an aluminum guide rod, a steel claw and a prebaked carbon block. The steel claw is connected to the carbon block and the aluminum guide rod, bears the weight of the anode, and also transmits a strong current. At high temperatures of 400 to 900°C, the anode steel claw is easily corroded by the electrolyte, the electrode material, the air and the electrolytic flue gas. At the same time, it is also damaged by thermal stress, electromagnetic force and collision force, and is easily oxidized by high temperature and corroded by the electrolyte. The corrosion of the steel claw will not only shorten its service life and form a "thin waist" phenomenon, but also the corrosion products formed after the steel claw is corroded will enter the electrolyte, affecting the quality of the original aluminum, the distribution of the current, and the correct judgment of the operating conditions of the electrolytic cell. In addition, the corrosion of the steel claw increases the production cost of the anode steel claw to a certain extent.
[0003] At present, the main corrosion protection technologies for anode steel claws include protection ring technology, coating technology, and wrapping technology. Among them, the protection effect of the anti-corrosion materials in the coating on the anode steel claws is still not ideal. The main reason is that the anode steel claws involve a series of complex operations such as shelling, material cutting, pole replacement, and slag removal during use. Once the coating or protection ring of the anode steel claw cracks or falls off, the protection of the steel claw will be lost. Therefore, reducing the corrosion of the anode steel claw is of great significance to extending the service life of the steel claw, improving the quality of raw aluminum, and reducing production costs. Summary of the invention
[0004] The present application provides an anti-corrosion composition, a paint, a coating and an anode steel claw to solve the following technical problem: how to improve the high-temperature gas corrosion resistance of the anti-corrosion composition.
[0005] In a first aspect, the present application provides an anti-corrosion composition, wherein the raw materials of the anti-corrosion composition include: anti-corrosion filler, and the raw materials of the anti-corrosion composition include: hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon micropowder and quartz sand;
[0006] In the anti-corrosion composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silicon micropowder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight.
[0007] In a second aspect, the present application provides a coating, the raw materials of which include the anti-corrosion composition described in any one of the first aspects.
[0008] Optionally, the weight of the anti-corrosion composition is 50% to 70% of the total weight of the raw materials of the coating.
[0009] Optionally, the raw materials of the coating also include: a catalyst, an adhesive, an emulsifier and an additive.
[0010] Optionally, the adhesive includes an inorganic adhesive and an organic adhesive; and / or,
[0011] The catalyst comprises at least one of the following: yttrium oxide, titanium oxide, cerium oxide; and / or,
[0012] The emulsifier includes at least one of the following: vinyl acetate emulsion, acrylic emulsion, polyurethane emulsion.
[0013] Optionally, the organic adhesive includes at least one of the following: epoxy resin, phenolic resin, furan resin; and / or,
[0014] The inorganic adhesive includes at least one of the following: silica sol, sodium silicate, and potassium silicate.
[0015] Optionally, the auxiliary agent includes at least one of the following: a thickener, a dispersant, a defoaming agent, a leveling agent, and a high temperature resistant metal ceramic transition agent.
[0016] Optionally, in the coating, the anti-corrosion composition is 50 to 70 parts by weight, the catalyst is 2 to 6 parts by weight, the adhesive is 21 to 40 parts by weight, the emulsifier is 1 to 7 parts by weight, and the auxiliary agent is 4 to 10 parts by weight.
[0017] In a third aspect, the present application provides a coating, wherein the coating is formed by the coating described in any one of the second aspects.
[0018] In a fourth aspect, the present application provides an anode steel claw, comprising an anode steel claw substrate and the coating according to the third aspect attached to at least a portion of the surface of the anode steel claw substrate.
[0019] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0020] The anti-corrosion composition provided in the embodiment of the present application comprises raw materials of: hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon micropowder and quartz sand; in the anti-corrosion composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silicon micropowder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight. The main components of hard clay include Al2O3 and SiO2, and it has a dense structure and uniform texture, as well as the advantages of stable chemical properties and sintering resistance, which can effectively prevent the contact between high-temperature gas and the protected substrate; kaolin has good heat resistance, plasticity and dispersibility, so as to improve the high-temperature plasticity of the anti-corrosion composition; the alkali metal ions in potassium fluoroaluminate and sodium hexametaphosphate can adjust the modulus ratio of the anti-corrosion composition, thereby improving the viscosity and high-temperature anti-corrosion performance of the anti-corrosion composition; borax will melt at high temperature and form a glassy substance, thereby adjusting the melting state of the anti-corrosion composition at high temperature and improving the high-temperature viscosity of the anti-corrosion composition; the main components of silicon micropowder and quartz sand are SiO2, which can adjust the anti-corrosion composition modulus ratio, and under high temperature environment, SiO2 promotes the formation of a very thin and dense oxide film on the surface of the substrate, which can effectively prevent oxygen from further diffusing into the interior, slow down the oxidation reaction, and improve the high temperature gas corrosion resistance of the anti-corrosion composition, and silicon powder and quartz sand can coordinately adjust the particle size distribution, fully fill the gaps in the coating, thereby improving the strength of the anti-corrosion composition; and the content of each raw material in the anti-corrosion composition is reasonably designed, and under the action of kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon powder and quartz sand, the plasticity, melting point and viscosity of hard clay at high temperature are adjusted, so as to better play the high temperature gas corrosion resistance of hard clay, thereby improving the high temperature gas corrosion resistance of the anti-corrosion composition. Therefore, the anti-corrosion composition, as a raw material of the coating, can improve the high temperature gas corrosion resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0023] Figure 1A schematic flow chart of a method for preparing a coating provided in an embodiment of the present application. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0026] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following (individuals)" or similar expressions thereof refer to any combination of these items, including any combination of singular (individuals) or plural (individuals). For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Weight parts expression" such as weight parts, mass parts, etc., represents the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the weight ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the weight of substance A: the weight of substance B: the weight of substance C = 1:2:3.
[0027] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0028] In a first aspect, the present application provides an anti-corrosion composition, the raw materials of which include: hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon micropowder and quartz sand;
[0029] In the anti-corrosion composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silicon micropowder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight.
[0030] In the present application embodiment, hard clay is a refractory clay formed by sedimentation. The main components of hard clay include Al2O3 and SiO2, and have a dense structure and uniform texture, as well as the advantages of chemical stability and sintering resistance (refractory greater than 1750°C), which can effectively block the contact between high-temperature gas and the protected substrate. The hard clay can be 55 parts by weight to 70 parts by weight, so as to fully realize the anti-high-temperature gas corrosion performance of the hard clay, while avoiding the risk of cracking of the coating formed by the anti-corrosion composition due to the hard clay exceeding 70 parts by weight. Exemplary, the hard clay can be 55 parts by weight, 57 parts by weight, 59 parts by weight, 61 parts by weight, 63 parts by weight, 65 parts by weight, 67 parts by weight, 69 parts by weight, 70 parts by weight, etc.
[0031] The main components of kaolin are Al4[Si4O 10 ](OH)8 is a hydrous aluminum silicate mineral belonging to the triclinic system. There are no cations or water molecules in the crystal structure. The layers are connected by hydrogen bonds. It has good heat resistance, plasticity and dispersibility, and can improve the high-temperature plasticity of the anti-corrosion composition. Kaolin can be 5 to 15 parts by weight, so that the Al / Si ratio in the entire anti-corrosion composition can be adjusted to ensure the reactivity of the anti-corrosion composition and improve the high-temperature plasticity of the anti-corrosion composition. Exemplarily, the kaolin can be 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, 11 parts by weight, 12 parts by weight, 13 parts by weight, 14 parts by weight, 15 parts by weight, etc.
[0032] Potassium fluoroaluminate has high viscosity and strength, and can adjust the proportion of alkali metal cations in the anti-corrosion composition, thereby adjusting the modulus ratio of the anti-corrosion composition. Potassium fluoroaluminate can be 5 to 10 parts by weight, fully achieving the purpose of adjusting the modulus ratio of the anti-corrosion composition and improving the high-temperature protection performance of the anti-corrosion composition. The above modulus ratio represents the molar ratio of alkali metal to silicon dioxide in the anti-corrosion composition, and the modulus ratio affects the high-temperature protection performance, hardness, plasticity and chemical stability of the anti-corrosion composition. Exemplarily, the potassium fluoroaluminate can be 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, etc.
[0033] Sodium hexametaphosphate has low viscosity and strength, but good solubility in water, and can adjust the ratio of alkali metal cations in the anti-corrosion composition. Sodium hexametaphosphate can be 5 to 10 parts by weight, which can fully adjust the modulus ratio of the anti-corrosion composition and increase the viscosity of the anti-corrosion composition, and improve the high-temperature protection performance of the anti-corrosion composition. Exemplarily, the sodium hexametaphosphate can be 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, etc.
[0034] Borax will melt at high temperatures and form a glassy substance, thereby adjusting the melting state of the coating at high temperatures and increasing the high-temperature viscosity of the coating. Borax can be 2 parts by weight to 8 parts by weight, which fully makes the anti-corrosion composition molten at high temperatures, while avoiding that the coating formed by the anti-corrosion composition falls off and fails at high temperatures due to the borax exceeding 8 parts by weight. Exemplarily, the borax can be 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, etc.
[0035] The main components of silicon micropowder and quartz sand are SiO2, which can adjust the modulus ratio of the anti-corrosion composition. In addition, under high temperature environment, SiO2 promotes the formation of a very thin and dense oxide film on the surface of the substrate, which can effectively prevent oxygen from further diffusing into the interior, slow down the oxidation reaction, and improve the anti-high temperature gas corrosion performance of the anti-corrosion composition. The particles of silicon micropowder are extremely fine, with a particle size of up to submicron level, high purity and good insulation; the particles of quartz sand are larger, with a wide range of particle sizes, high hardness and high mechanical strength. Therefore, silicon micropowder and quartz sand can coordinately adjust the particle size grading, fully fill the gaps of the anti-corrosion composition, and thus improve the strength of the anti-corrosion composition. The silicon micropowder can be 1 to 6 parts by weight, and the quartz sand can be 1 to 6 parts by weight, which fully realizes the coordinated adjustment of the particle size grading of silicon micropowder and quartz sand, reduces the porosity of the anti-corrosion composition, and improves the strength of the anti-corrosion composition. Illustratively, the amount of silicon micropowder can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, etc., and the amount of quartz sand can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, etc.
[0036] Therefore, the content of each raw material in the anti-corrosion composition is reasonably designed, and the plasticity, melting point and viscosity of the hard clay at high temperature are adjusted under the action of kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silicon micropowder and quartz sand, so as to better exert the anti-high temperature gas corrosion performance of the hard clay, thereby improving the anti-high temperature gas corrosion performance of the anti-corrosion composition.
[0037] In a second aspect, the present application provides a coating, the raw materials of which include the anti-corrosion composition described in any one of the first aspects.
[0038] In the embodiments of the present application, the anti-corrosion composition is used as a raw material of a coating to improve the coating's anti-high temperature gas corrosion performance.
[0039] The coating is realized based on the above-mentioned anti-corrosion composition. The specific raw materials of the anti-corrosion composition can refer to the above-mentioned embodiments. Since the coating adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0040] In some embodiments, the weight of the anti-corrosion composition is 50% to 70% of the total weight of the raw materials of the coating.
[0041] In the embodiment of the present application, the weight of the anti-corrosion composition can be 50% to 70% of the total weight of the raw materials of the coating, so as to fully realize the anti-high temperature gas corrosion protection effect of the anti-corrosion composition. Exemplarily, the weight of the anti-corrosion composition can be 50%, 55%, 60%, 65%, 70%, etc. of the total weight of the raw materials of the coating.
[0042] In some embodiments, the raw materials of the coating further include: a catalyst, an adhesive, an emulsifier and an additive.
[0043] In some embodiments, the adhesive comprises an inorganic adhesive and an organic adhesive; and / or,
[0044] The catalyst comprises at least one of the following: yttrium oxide, titanium oxide, cerium oxide; and / or,
[0045] The emulsifier includes at least one of the following: vinyl acetate emulsion, acrylic emulsion, polyurethane emulsion.
[0046] In some embodiments, the organic binder includes at least one of the following: epoxy resin, phenolic resin, furan resin; and / or,
[0047] The inorganic adhesive includes at least one of the following: silica sol, sodium silicate, and potassium silicate.
[0048] In the embodiment of the present application, the raw materials of the coating may also include: a catalyst, an adhesive, an emulsifier and an auxiliary agent. The adhesive may include an inorganic adhesive and an organic adhesive. The synergistic effect of the organic adhesive and the inorganic adhesive enables the coating to have both good room temperature bonding strength and excellent high temperature bonding strength. The organic adhesive may be a combination of one or more of epoxy resin, phenolic resin, and furan resin; the inorganic adhesive may be a combination of one or more of silica sol, sodium silicate, and potassium silicate. The weight ratio of the inorganic adhesive to the organic adhesive may be (18-35): (2-15), so that the coating has excellent bonding strength at both room temperature and high temperature, and the organic adhesive decomposes and volatilizes under high temperature conditions without affecting the high temperature performance of the coating. Exemplarily, the catalyst may be a combination of one or more of yttrium oxide, titanium oxide, and cerium oxide, and the emulsifier may be a combination of one or more of vinyl acetate emulsion, acrylic emulsion, and polyurethane emulsion.
[0049] In some embodiments, the auxiliary agent includes at least one of the following: a thickener, a dispersant, a defoaming agent, a leveling agent, and a high temperature resistant metal ceramic transition agent.
[0050] In the embodiment of the present application, the auxiliary agent can be a combination of one or more of a thickener, a dispersant, a defoamer, a leveling agent, and a high temperature resistant metal ceramic transition agent. Among them, the thickener can increase the viscosity of a fluid or semi-fluid to make it thicker, and the thickener can reduce the fluidity of the coating and increase the viscosity; the dispersant can be used to prevent solid particles from agglomerating in a liquid and make the particles evenly dispersed; the defoamer is a substance used to eliminate or inhibit the generation of foam in a liquid system; the leveling agent can improve the surface leveling properties of coating materials such as coatings and inks; the high temperature resistant metal ceramic transition coating can overcome the surface tension generated on the metal surface when the coating is applied, or seal the tiny gaps in the material to increase the adhesion of the coating.
[0051] In some embodiments, based on the total weight of the raw materials of the coating, the anti-corrosion composition is 50 to 70 parts by weight, the catalyst is 2 to 6 parts by weight, the adhesive is 21 to 40 parts by weight, the emulsifier is 1 to 7 parts by weight, and the auxiliary agent is 4 to 10 parts by weight.
[0052] In the embodiment of the present application, the anticorrosion composition can be 50 to 70 parts by weight, so as to fully realize the role of the anticorrosion composition in preventing high temperature gas corrosion. The catalyst can be 2 to 6 parts by weight, so as to increase the reactivity of the coating under high temperature conditions and accelerate the reaction rate. The adhesive can be 21 to 40 parts by weight, so that the coating has a bonding effect at room temperature and high-temperature solid phase sintering occurs. The emulsifier can be 1 to 7 parts by weight, so as to adjust the state of the coating, change the surface tension and permeability of the coating, and better wet the substrate, so as to improve the adhesion of the coating. The auxiliary agent can be 4 to 10 parts by weight, so as to improve the thermal matching state of the coating and the steel claw, and reduce the risk of cracking of the coating caused by the different expansion coefficients of the coating and the steel claw. Exemplarily, the anti-corrosion composition can be 50 parts by weight, 55 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, etc., the catalyst can be 2 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, etc., the adhesive can be 21 parts by weight, 23 parts by weight, 26 parts by weight, 30 parts by weight, 33 parts by weight, 36 parts by weight, 40 parts by weight, etc., the emulsifier can be 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, etc., and the auxiliary agent can be 4 parts by weight, 5 parts by weight, 6 parts by weight, 7 parts by weight, 8 parts by weight, 9 parts by weight, 10 parts by weight, etc.
[0053] Figure 1 A schematic diagram of a method for preparing a coating provided in an embodiment of the present application; see Figure 1The preparation method of the above-mentioned coating comprises: S1, mixing the anti-corrosion composition and the catalyst for the first time to obtain a first mixed material; S2, mixing the binder, the emulsifier and the auxiliary agent for the second time to obtain a second mixed material; S3, mixing the first mixed material and the second mixed material for the third time to obtain the coating.
[0054] In a third aspect, the present application provides a coating, wherein the coating is formed by the coating described in any one of the second aspects.
[0055] In the embodiments of the present application, the coating can have a good bonding effect at room temperature, so that the coating is evenly and densely attached to the surface of the substrate to form a coating, and the coating can be obtained by naturally curing the coating at room temperature for 2 hours.
[0056] The coating is realized based on the above-mentioned coating. The specific raw materials of the coating can refer to the above-mentioned embodiments. Since the coating adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0057] In a fourth aspect, the present application provides an anode steel claw, comprising an anode steel claw substrate and the coating according to the third aspect attached to at least a portion of the surface of the anode steel claw substrate.
[0058] In the embodiments of the present application, under high temperature conditions, the organic components in the coating volatilize, and the inorganic components undergo solid-phase sintering. Under aluminum electrolysis conditions, the hard clay in the coating reacts chemically with the electrolyte gas fluoride (sodium fluoride) to form a nepheline layer. The nepheline layer usually has a certain density and hardness. This dense structure can prevent the penetration of oxygen and fluorinated gases and act as a physical barrier. Nepheline has a certain high-temperature stability and can effectively block the oxidation of the steel claw material by high-temperature oxygen and the corrosion of the steel claw material by fluorinated gases, forming a good protective layer for the steel claw substrate, thereby increasing the service life of the steel claw.
[0059] The anode steel claw is realized based on the above-mentioned coating. The specific coating raw materials of the coating can refer to the above-mentioned embodiment. Since the anode steel claw adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.
[0060] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.
[0061] Example 1
[0062] An anti-corrosion composition comprises raw materials: 62 parts by weight of hard clay, 12 parts by weight of kaolin, 6 parts by weight of potassium fluoroaluminate, 7 parts by weight of sodium hexametaphosphate, 5 parts by weight of borax, 4 parts by weight of silicon micropowder, and 4 parts by weight of quartz sand, with a particle size of 0.5 μm-2 μm and a spherical shape.
[0063] A coating, the raw materials of which include: 60 parts by weight of an anti-corrosion composition; 3 parts of a catalyst, which is titanium oxide, has a particle size of 0.1 μm-1 μm, and is spherical in shape; 27 parts by weight of an inorganic adhesive, which is 60 parts by weight of sodium silicate and 40 parts by weight of silica sol; 2 parts by weight of an organic adhesive, which is phenolic resin; 2 parts by weight of an emulsifier, which is acrylic emulsion; 6 parts by weight of an auxiliary agent, which is 5 parts by weight of a thickener, 5 parts by weight of a dispersant, 2 parts by weight of a pH regulator, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 84 parts by weight of a high-temperature resistant metal ceramic transition agent.
[0064] A method for preparing a coating comprises: loading various raw materials and a catalyst of an anti-corrosion composition into a three-dimensional mixer to mix powder materials, wherein the mixing parameters are a frequency of 35 Hz, a rotation speed of 20 r / min, and a time of 30 minutes, to obtain a first mixed material; loading an adhesive, an emulsifier, and an auxiliary agent into a magnetic heating stirrer to stir and mix the liquid, wherein the stirring parameters are a rotation speed of 40 r / min, a temperature of 70°C, and a time of 50 minutes, to obtain a second mixed material; and uniformly stirring and mixing the first mixed material and the second mixed material to obtain a coating.
[0065] Aluminum electrolytic anode steel claws: The surface of aluminum electrolytic anode steel claws is pretreated to remove surface dirt and obtain a clean surface; the coating is applied to the surface of the steel claws by hand brushing, and naturally cured at room temperature for 2 hours. The coating thickness is 1.6mm. Under the electrolytic condition of 950℃, the coating can form an anti-oxidation and corrosion-resistant protective layer on the surface of the steel claws. The coating is uniform and dense, and plays an effective anti-oxidation role, which can reduce the oxidation corrosion rate of the steel claws from 2mm / cycle to 0.3mm / cycle.
[0066] Example 2
[0067] An anti-corrosion composition comprises raw materials: 64 parts by weight of hard clay, 11 parts by weight of kaolin, 6 parts by weight of potassium fluoroaluminate, 6 parts by weight of sodium hexametaphosphate, 5 parts by weight of borax, 5 parts by weight of silicon micropowder, and 3 parts by weight of quartz sand. The particle size is 0.5 μm-2 μm and the shape is spherical.
[0068] A coating, the raw materials of which include: 58 parts by weight of an anti-corrosion composition; 2 parts by weight of a catalyst, which is titanium oxide, has a particle size of 0.1 μm-1 μm, and is spherical in shape; 28 parts by weight of an inorganic adhesive, which is 70 parts by weight of sodium silicate and 30 parts by weight of potassium silicate; 4 parts by weight of an organic adhesive, which is phenolic resin; 2 parts by weight of an emulsifier, which is acrylic emulsion; 6 parts by weight of an auxiliary agent, which is 5 parts by weight of a thickener, 5 parts by weight of a dispersant, 2 parts by weight of a pH regulator, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 84 parts by weight of a high-temperature resistant metal ceramic transition agent.
[0069] A method for preparing a coating comprises: loading various raw materials and a catalyst of an anti-corrosion composition into a three-dimensional mixer to mix powder materials, wherein the mixing parameters are a frequency of 30 Hz, a rotation speed of 25 r / min, and a time of 25 minutes, to obtain a first mixed material; loading an adhesive, an emulsifier, and an auxiliary agent into a magnetic heating stirrer to stir and mix the liquid, wherein the stirring parameters are a rotation speed of 26 r / min, a temperature of 60°C, and a time of 40 minutes, to obtain a second mixed material; and uniformly stirring and mixing the first mixed material and the second mixed material to obtain a coating.
[0070] Aluminum electrolytic anode steel claws: The surface of aluminum electrolytic anode steel claws is pretreated to remove surface dirt and obtain a clean surface; the coating is applied to the surface of the steel claws by pressure spraying, and naturally cured at room temperature for 2 hours. The coating thickness is 0.8mm. Under the electrolytic condition of 950℃, the coating can form an anti-oxidation and corrosion-resistant protective layer on the surface of the steel claws. The coating is uniform and dense, and plays an effective anti-oxidation role, which can reduce the oxidation corrosion rate of the steel claws from 2mm / cycle to 0.5mm / cycle.
[0071] Example 3
[0072] An anti-corrosion composition comprises raw materials of: 67 parts by weight of hard clay, 10 parts by weight of kaolin, 5 parts by weight of potassium fluoroaluminate, 6 parts by weight of sodium hexametaphosphate, 4 parts by weight of borax, 5 parts by weight of silicon micropowder, 3 parts by weight of quartz sand, with a particle size of 0.5 μm-2 μm and a spherical shape.
[0073] A coating, calculated by weight, comprises: 56 parts by weight of an anti-corrosion composition; 3 parts by weight of a catalyst, which is 100% by weight of oxide, has a particle size of 0.1 μm-1 μm, and is spherical in shape; 28 parts by weight of an inorganic adhesive, which is 20 parts by weight of sodium silicate, 30 parts by weight of potassium silicate, and 50 parts by weight of silica sol; 4 parts by weight of an organic adhesive, which is a furan resin; 3 parts by weight of an emulsifier, which is a vinyl acetate emulsion; 6 parts by weight of an auxiliary agent, which is 3 parts by weight of a thickener, 3 parts by weight of a dispersant, 2 parts by weight of a pH adjuster, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent, and 88 parts by weight of a high-temperature resistant metal ceramic transition agent.
[0074] A method for preparing a coating comprises: loading various raw materials and a catalyst of an anti-corrosion composition into a three-dimensional mixer to mix powder materials, wherein the mixing parameters are a frequency of 30 Hz, a rotation speed of 25 r / min, and a time of 30 minutes, to obtain a first mixed material; loading an adhesive, an emulsifier, and an auxiliary agent into a magnetic heating stirrer to stir and mix the liquid, wherein the stirring parameters are a rotation speed of 30 r / min, a temperature of 55°C, and a time of 35 minutes, to obtain a second mixed material; and uniformly stirring and mixing the first mixed material and the second mixed material to obtain a coating.
[0075] Aluminum electrolytic anode steel claws: The surface of aluminum electrolytic anode steel claws is pretreated to remove surface dirt and obtain a clean surface; the coating is applied to the surface of the steel claws by pressure spraying, and naturally cured at room temperature for 2 hours. The coating thickness is 1mm. Under the electrolytic condition of 950℃, the coating can form an anti-oxidation and corrosion-resistant protective layer on the surface of the steel claws. The coating is uniform and dense, and plays an effective anti-oxidation role, which can reduce the oxidation corrosion rate of the steel claws from 2mm / cycle to 0.6mm / cycle.
[0076] Example 4
[0077] An anti-corrosion composition comprises raw materials of: 58 parts by weight of hard clay, 12 parts by weight of kaolin, 8 parts by weight of potassium fluoroaluminate, 8 parts by weight of sodium hexametaphosphate, 4 parts by weight of borax, 5 parts by weight of silicon micropowder, 5 parts by weight of quartz sand, with a particle size of 0.5 μm-4 μm and a spherical shape.
[0078] A coating, the raw materials of which include: 62 parts by weight of an anti-corrosion composition; 2 parts by weight of a catalyst, which is cerium oxide with a particle size of 0.1 μm-1 μm and a spherical shape; 28 parts by weight of an inorganic adhesive, which is 20 parts by weight of sodium silicate, 30 parts by weight of potassium silicate and 50 parts by weight of silica sol; 2 parts by weight of an organic adhesive, which is furan resin; 2 parts by weight of an emulsifier, which is a polyurethane emulsion; 4 parts by weight of an auxiliary agent, which is 4 parts by weight of a thickener, 4 parts by weight of a dispersant, 2 parts by weight of a pH regulator, 1 part by weight of a defoamer, 3 parts by weight of a leveling agent and 86 parts by weight of a high-temperature resistant metal ceramic transition agent.
[0079] A method for preparing a coating comprises: loading various raw materials and a catalyst of an anti-corrosion composition into a three-dimensional mixer to mix powder materials, wherein the mixing parameters are a frequency of 40 Hz, a rotation speed of 25 r / min, and a time of 35 minutes, to obtain a first mixed material; loading an adhesive, an emulsifier, and an auxiliary agent into a magnetic heating stirrer to stir and mix the liquid, wherein the stirring parameters are a rotation speed of 35 r / min, a temperature of 55°C, and a time of 40 minutes, to obtain a second mixed material; and uniformly stirring and mixing the first mixed material and the second mixed material to obtain a coating.
[0080] Aluminum electrolytic anode steel claws: The surface of aluminum electrolytic anode steel claws is pretreated to remove surface dirt and obtain a clean surface; the coating is applied to the surface of the steel claws by pressure spraying, and naturally cured at room temperature for 2 hours. The coating thickness is 1mm. Under the electrolytic condition of 950℃, the coating can form an anti-oxidation and corrosion-resistant protective layer on the surface of the steel claws. The coating is uniform and dense, and plays an effective anti-oxidation role, which can reduce the oxidation corrosion rate of the steel claws from 2mm / cycle to 0.5mm / cycle.
[0081] Comparative Example 1
[0082] Based on the disclosure of Example 1, the difference between Comparative Example 1 and Example 1 is that: 13 parts by weight of sodium hexametaphosphate and no potassium fluoroaluminate.
[0083] Under electrolytic conditions at 950°C, the coating can reduce the oxidation corrosion rate of steel claws from 2 mm / cycle to 1.8 mm / cycle.
[0084] Comparative Example 2
[0085] Based on the disclosure of Example 1, Comparative Example 2 differs from Example 1 in that: 50 parts by weight of hard clay and 24 parts by weight of kaolin.
[0086] Under electrolytic conditions at 950°C, the coating can reduce the oxidation corrosion rate of steel claws from 2 mm / cycle to 1.7 mm / cycle.
[0087] Comparative Example 3
[0088] Based on the disclosure of Example 1, Comparative Example 3 differs from Example 1 in that: 8 parts by weight of silicon micropowder is used, and there is no quartz sand.
[0089] Under electrolytic conditions at 950°C, the coating can reduce the oxidation corrosion rate of steel claws from 2 mm / cycle to 1.8 mm / cycle.
[0090] Note: In the above Examples 1 to 4 and Comparative Examples 1 to 3, the thickener is Ocean Haiderun DH-02, the dispersant is Ocean Haiderun 5040, the pH adjuster is Dow AMP-95, the defoamer is tributyl phosphate type defoamer), the leveling agent is Dow RM-2020NPR, and the high temperature resistant metal ceramic transition agent is Zhisheng Weihua model ZS-1001.
[0091] It can be seen from Examples 1 to 4 and Comparative Examples 1 to 3 that the coating of the anode steel claw provided in the embodiments of the present application has an oxidation corrosion rate of less than 0.6 mm, so that the coating can play a good protective role for the anode steel claw in aluminum electrolysis.
[0092] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:
[0093] (1) The coating provided in the embodiments of the present application has excellent anti-oxidation properties and can effectively resist the oxidation of steel claws by high-temperature gas under aluminum electrolysis conditions, reducing the oxidation of steel claws by 90%;
[0094] (2) The coating provided in the embodiments of the present application has excellent anti-corrosion properties and can form a nepheline layer with fluorides in high-temperature gases to prevent the corrosion of the anode steel claws by the fluorinated gases.
[0095] (3) The coating provided in the embodiments of the present application has excellent thermal shock resistance, has strong bonding strength with the steel claw substrate under the conditions of 500°C to 900°C, and the coating does not crack or detach.
[0096] (4) The coating provided in the embodiment of the present application can increase the service life of the anode steel claw by more than 2 times, which can not only reduce the Fe impurity content in the aluminum liquid, but also be beneficial to the production of high-quality primary aluminum products and increase the added value of the products; at the same time, it can also reduce the occurrence of the thin waist phenomenon of the steel claw, reduce the pressure drop of the steel claw, reduce the energy consumption of aluminum electrolysis, and reduce the production cost of the enterprise.
[0097] (5) The coating provided in the embodiments of the present application is simple to prepare and operate, low in cost, and easy to industrialize. It can be directly applied by brushing or cold spraying. The use process is simple and convenient, which has positive significance for saving steel materials and reducing production costs in the aluminum electrolysis industry.
[0098] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. An anti-corrosion composition, the raw materials of the anti-corrosion composition comprising: Hard clay, kaolin, potassium fluoroaluminate, sodium hexametaphosphate, borax, silica powder and quartz sand; In the anti-corrosion composition, the hard clay is 55 to 70 parts by weight, the kaolin is 5 to 15 parts by weight, the potassium fluoroaluminate is 5 to 10 parts by weight, the sodium hexametaphosphate is 5 to 10 parts by weight, the borax is 2 to 8 parts by weight, the silicon micropowder is 1 to 6 parts by weight, and the quartz sand is 1 to 6 parts by weight.
2. A coating, wherein the raw material of the coating comprises the anti-corrosion composition according to claim 1.
3. The coating according to claim 2, characterized in that The weight of the anti-corrosion composition is 50% to 70% of the total weight of the raw materials of the coating.
4. The coating according to claim 2, characterized in that The raw materials of the coating also include: a catalyst, an adhesive, an emulsifier and an auxiliary agent.
5. The coating according to claim 4, characterized in that The adhesive includes an inorganic adhesive and an organic adhesive; and / or, The catalyst comprises at least one of the following: yttrium oxide, titanium oxide, cerium oxide; and / or, The emulsifier includes at least one of the following: vinyl acetate emulsion, acrylic emulsion, polyurethane emulsion.
6. The coating according to claim 5, characterized in that The organic adhesive comprises at least one of the following: epoxy resin, phenolic resin, furan resin; and / or, The inorganic adhesive includes at least one of the following: silica sol, sodium silicate, and potassium silicate.
7. The coating according to claim 4, characterized in that The auxiliary agent includes at least one of the following: a thickener, a dispersant, a defoamer, a leveling agent, and a high temperature resistant metal ceramic transition agent.
8. The coating according to claim 4, characterized in that In the coating, the anticorrosion composition is 50 to 70 parts by weight, the catalyst is 2 to 6 parts by weight, the adhesive is 21 to 40 parts by weight, the emulsifier is 1 to 7 parts by weight, and the auxiliary agent is 4 to 10 parts by weight.
9. A coating layer, the coating layer being formed from the coating material according to any one of claims 2 to 8. 10 . An anode steel claw, comprising an anode steel claw substrate and the coating according to claim 9 attached to at least a portion of the surface of the anode steel claw substrate.
Citation Information
Patent Citations
Coating material on fireproof material for continuous casting device and use method thereof
CN103130521A
High temperature aluminium liquid corrosion resistant paint, and preparation method thereof
CN109704577A
Organic-inorganic composite waterborne aluminum powder paint and preparation method thereof
CN109868015A
Antioxidant coating for electrolytic aluminum anode, coating and electrolytic aluminum anode
CN118620427A